If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7f + 10 = 8f Reorder the terms: 10 + 7f = 8f Solving 10 + 7f = 8f Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-8f' to each side of the equation. 10 + 7f + -8f = 8f + -8f Combine like terms: 7f + -8f = -1f 10 + -1f = 8f + -8f Combine like terms: 8f + -8f = 0 10 + -1f = 0 Add '-10' to each side of the equation. 10 + -10 + -1f = 0 + -10 Combine like terms: 10 + -10 = 0 0 + -1f = 0 + -10 -1f = 0 + -10 Combine like terms: 0 + -10 = -10 -1f = -10 Divide each side by '-1'. f = 10 Simplifying f = 10
| 4/7x(-2/9) | | -3v-7=-4 | | 9x-5=-nx-mx+mn | | 25w^2-4w=0 | | 8x+20=y | | 2q-8=3q | | 2w^2-2= | | 22-10=n | | 6u=-4u+10 | | 0.5*5+4=4.5 | | c=35-18 | | w^2-w-2= | | 1.5x+.66x=13 | | -(7/5)X=49 | | n-34=26 | | -8w=-7w+9 | | 10-d/5=10 | | 8+6k=50 | | y=24/8 | | 5(v-6)-7v=-10 | | .6x-.6=3 | | .5x-.2x=3 | | 8x^2y-4xy^2= | | 5v^2-20= | | 4/14 | | 2x+x-4(12-9)+2*2= | | 6x-(4+2x)=2(x+2) | | Logx^5=45 | | 7(x+4)=5+7x | | 1/2p-3=1 | | 6-h/2=10 | | b+9=y |